Study on the Influence of Various Rainfall Types on the Stability of High and Steep Slopes. (7th December 2021) - Qian, Jin; Sun, Ding; Li, Guodong; Wu, Yue
Abstract : Taking the high and steep slope of a ski resort as the background, in order to ensure the structural safety of the slope in the subsequent complex rainfall environment, the calculation principle of unsaturated soil slope stability is summarized, and the parameter interaction analysis is proposed. The numerical simulation method is used to study the influence of various rainfall types on slope stability; combined with a multiparameter combination, the slope stability is analyzed. The results show that different types of rainfall have a significant impact on the safety factor of the slope, the safety factor of the slope under the front rainfall type is the smallest, the minimum value is 1.38, and the front rainfall mostly occurs in the late summer, so it is necessary to avoid construction in the late summer or do a good job of safety monitoring in the late summer. Through setting monitoring points, it is found that the pore water pressure of the three positions from small to large is in the order of slope toe<slope middle<slope top, and the pore water pressure at the slope toe is basically 0 kPa. At this time, the matric suction at the slope toe is the minimum, so the protection should be strengthened. In the combination analysis of the four parameters, the direct effect and coupling effect of C15 are at a small level, which indicates that when the four parameters fluctuate together, the mutual coupling is not the effect of a single parameter, which provides a theoretical reference for the follow-up related research.